2019
DOI: 10.3390/ijerph16214277
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Respiratory Health Symptoms among Landfill Waste Recyclers in the City of Johannesburg, South Africa

Abstract: In developing countries, waste sorting and recycling have become a source of income for poorer communities. However, it can potentially pose significant health risks. This study aimed to determine the prevalence of acute respiratory symptoms and associated risk factors for respiratory health outcomes among waste recyclers. A cross-sectional study was conducted among 361 waste recyclers at two randomly selected landfill sites in Johannesburg. Convenience sampling was used to sample the waste recyclers. The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Of the 36 micro-level research studies, the majority were studies conducted in LMICs (29, 80.6%). Diverse types of informal workers were studied in LMICs, including waste workers [ 16 21 ], trash pickers [ 22 ], clay artisans [ 23 ], taxi drivers [ 24 ], artisanal and small-scale gold miners [ 25 ], informal commerce workers [ 26 ], female beer promoters [ 27 ], domestic workers [ 28 ], informal fisheries [ 29 ], and informal workers in the construction and manufacturing industry [ 30 37 ]. The remaining micro-level studies were conducted in LMICs [ 38 43 ] and HIC contexts [ 9 ], rather than focusing on a specific type of informal workers, and analyzed survey data or injury reports to examine the difference in health outcomes between workers in informal and formal employment.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 micro-level research studies, the majority were studies conducted in LMICs (29, 80.6%). Diverse types of informal workers were studied in LMICs, including waste workers [ 16 21 ], trash pickers [ 22 ], clay artisans [ 23 ], taxi drivers [ 24 ], artisanal and small-scale gold miners [ 25 ], informal commerce workers [ 26 ], female beer promoters [ 27 ], domestic workers [ 28 ], informal fisheries [ 29 ], and informal workers in the construction and manufacturing industry [ 30 37 ]. The remaining micro-level studies were conducted in LMICs [ 38 43 ] and HIC contexts [ 9 ], rather than focusing on a specific type of informal workers, and analyzed survey data or injury reports to examine the difference in health outcomes between workers in informal and formal employment.…”
Section: Resultsmentioning
confidence: 99%
“…* Specifically they were asked whether they handled household detergents, paint and pesticide containers. Tlotleng et al (2019) also reported a high prevalence of interaction between waste pickers on South African dumpsites and chemical substances, finding a statistically significant (p = 0.001) correlation between this exposure and respiratory symptoms ( (Jusko et al, 2008;Koller et al, 2004;Schnaas et al, 2006). It is noted that teenagers are considered as particularly vulnerable to lead poisoning, because they highly absorb it (Grigg, 2004;Safi et al, 2006).…”
Section: Risk Characterisation For Biological Hazards On Land Disposamentioning
confidence: 96%
“…Heavy metals and metalloids are the most stabile pollutants in the environment. Mostly all metals and metalloids with different amount are hazardous, which not only endangers for the environment but also affect human health [9]. Heavy metals and metalloids are washed from waste…”
Section: Introductionmentioning
confidence: 99%